Mapping Publication Trends on Governance Capacity in Tourism Development: A Systematic Literature Review - Mursak, ‎; Nawawi, Juanda; Abdullah, Muh. Tang; Ibrahim, Muh. Akmal; Congge, Umar (KnE Social Sciences, 2025)
This study aims to map the development of research and scientific publications on capacity governance in tourism development. It uses a systematic literature review approach to analyze 46 scientific articles selected based on PRISMA procedures. The articles were sourced from the Scopus database published in the 2019–2024 period and analyzed with Vosviewer. The results reveal six topic clusters in the study of capacity governance towards tourism development, namely government, integration, sustainable tourism development, tourism sector, governance arrangement, and destination governance. Government is the most dominant cluster compared to other clusters, which indicates that it is a general concept used in the study of capacity governance in tourism development, and is related to various issues in other clusters, including sustainable development, tourism policy, policy implementation, destination governance, and destination development. This research contributes to the development of capacity governance studies in tourism development, sustainable tourism development, and destination governance. The limitation of this research is that the data used is only sourced from the Scopus database, so the results cannot explain the study of social movements on social media as a whole. Therefore, future research needs to use data or references from various reputable databases like Web of Science and EBSCO.